Clonagem e expressão de uma xilanase presente no (Meta)transcriptoma do Cupim da espécie Heterotermes tenuis e sua importante aplicação na produção de biocombustíveis - Ciancaglini, Iara (Universidade Federal de São Carlos, 2021)
Xylanases are an important group of enzymes responsible for the hydrolysis of the xylan glycosidic chain forming xylose and xylobiosis. Mainly noteworthy is endo-1,4-β-xylanase, a hemicellulase capable of cleaving the β-1,4 type glycosidic bond that exists in the hemicellulose chains present in the lignocellulosic material - bagasse and straw - resulting from the production of first generation ethanol. Its activity in the structure of hemicellulose is related to its application in the production of biofuels, because if produced and isolated, it can be used in the hydrolysis of biomass in the industrial production of second generation ethanol (2G). Such an enzyme can be found in a variety of genera of bacteria and yeasts, in addition to insects, protozoa and seaweed. Its application is varied and can be seen in other approaches, such as in the paper, food, feed and beverage industries. Termites are eusocial insects, with a high biomass degradation capacity, performing this task in hours, unlike fungi that can take weeks. Thus, these insects become potential targets in enzymatic bioprospecting. Studies carried out by our group analyzing the transcriptome of Brazilian termite species have identified several potential targets as essential genes for application in combating this insect as well as enzymes to be produced heterologously as the scope of this work. The species chosen for this study was Heterotermes tenuis, as it is a pest species of sugarcane, which is the raw material for the production of first and second generation ethanol. In addition, this species has nocturnal habits, which indicates the production of enzymes with different characteristics from those already known. In a previous analysis, sequences identified as possible endo-1,4-β-xylanase were detected. In this context, the main objective of this work was to amplify the coding region, clone and express this enzyme in a heterologous system, in order to evaluate its activity for a possible application in the production of second generation ethanol.
Cloning and expression of a xylanase present in the (Meta) transcriptom of the Termite species Heterotermes tenuis and its important application in the production of biofuels
Keywords: Cupim; Xilanase; Pichia pastoris; Expressão heteróloga; Etanol; Biocombustíveis; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR